2014
DOI: 10.4172/2329-6836.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activities of Compounds Isolated From Sida rhombifolia Linn. (Malvaceae)

Abstract: The main objective of this study was to isolate compounds from roots of Sida rhombifolia and subsequently evaluate their antibacterial activities. Crude gradient extracts were obtained from three solvents (petroleum ether, chloroform and methanol) with increasing solvent polarity using cold maceration technique. The in vitro antibacterial activity evaluation of gradient extracts and isolated compounds was done on four different pathogenic bacterial strains (Staphylococcus aureus, Escherichia coli, Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…The biological activities of these compounds are listed in Table 2 [23][24][25][26][27][28][29][30][31][32][33][34] . Reports suggest that compounds 9,12,15-octadecatrienoic acid-2,3-dihydroxy propyl ester [26] , sitosterol [28,29] , squalene [30,31] and ethyl iso-allocholate [33] have antimicrobial activity. We selected these four compounds for docking studies to reveal the binding orientation of ligands with the target.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activities of these compounds are listed in Table 2 [23][24][25][26][27][28][29][30][31][32][33][34] . Reports suggest that compounds 9,12,15-octadecatrienoic acid-2,3-dihydroxy propyl ester [26] , sitosterol [28,29] , squalene [30,31] and ethyl iso-allocholate [33] have antimicrobial activity. We selected these four compounds for docking studies to reveal the binding orientation of ligands with the target.…”
Section: Resultsmentioning
confidence: 99%
“…The active dichloromethane extracts were subjected to column chromatography over silica gel and sephadex LH-20. As the result, eleven coumarins osthole (1) (Sajjadi et al, 2009), imperatorin (2) (Muller et al, 2004), bergapten (3) (Stevenson et al, 2003), prantschimgin (4) (Sajjadi et al, 2015), grandivitinol (5) (Abyshe et al, 1977), suberosin (6) (Tabanca et al, 2016), xanthotoxin (7) (Stevenson et al, 2003), felamidin (8) (Kilic et al, 2006), marmesin (9) (Abreu et al, 2010), umbelliferone (10) (Singh et al, 2010), ulopterol (11) (Doganca et al, 1979) and a sterol mixture consisted of stigmasterol (12), β-sitosterol (13) (Woldeyes et al, 2012) (Figure 1) were isolated and identified.…”
Section: Resultsmentioning
confidence: 99%
“…13 β-Sitosterol (3a) and stigmasterol (3b) were also reported to possess antibacterial activities. 14,15,16,17 …”
Section: Resultsmentioning
confidence: 99%